A Strategic Plan for Collaborative Crisis Preparedness and Communication in Healthcare: Integrating Hospital Administration, Nursing Specialists, and Technicians for Effective Response - Deyab Hadi Alyami; Salem saleh ali alyami; Hassan Awad ali Alwadai; Abeer Hassan Alhayani; Fatima Yahya Ghazwani; Mashael Gamaan Alyami; Samirah Said Ali Alasmari; Samraa said Ali Alasmari; Hnadi moubark msoud alzogzog; Mariam Mohd Alamri (International Journal of Medical Toxicology and Legal Medicine, 2024)
The ability of healthcare organizations to respond effectively to crises has become increasingly vital in today’s unpredictable world. Crises, such as pandemics, natural disasters, or mass casualty incidents, put an immense strain on healthcare systems. These events require prompt, coordinated action across various sectors to ensure effective response, minimize harm, and optimize patient care. However, despite the urgency and complexity of such situations, many healthcare organizations still face significant challenges in ensuring that all sectors of the system are aligned and able to function together seamlessly. A key factor in overcoming these challenges is the collaboration between different stakeholders in the healthcare system, particularly hospital administration, nursing specialists, and technicians (Shmueli et al., 2021).